On The Job Skill-based Servant Leadership Training Model for Principal Effectiveness - Waruwu, Marinus; Komariah, Aan; Syaefudin Saud, Udin; Herawan, Endang (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to (1) develop an on-the-job, skill-based servant leadership training model in order to create effective principals in school management; (2) formulate the needs of the leadership training model for effective principals; and (3) determine the effectiveness of the leadership training model of on-the-job skill-based training. This research used Addie’s research and development method, including analysis of demands, design and development, implementation, and evaluation. The study subjects were principals. The results of the research show that (1) the training model is able to improve principal knowledge and skills. (2) Model variation obtains good category value. Material experts give value by 83.2% with a reliable category, media experts give value by 82.0% with a reliable category, and participants give value by 87.2% with a very reliable category. (3) Results of the post-test show a significant increase from the results of the pretest by achieving a mean of 79. Achievement of the posttest increases from a value of the pretest, which previously obtained 62. (4) Results of product trials through on-the-job learning obtain a mean score of 4.06. (5) Results of respondents’ responses to the training model obtain a mean score of 4.13. Based on the study results, it can be concluded that the on-the-job, skill-based servant leadership training model for principal effectiveness is reliable to be used as the principal training model. The training model encourages improved effective service leadership competence for school management.